Virtual leadership? The echurch as a South African case in point - Nell, Ian (HTS teologiese studies, 2016)
One of the most basic understandings of leadership relates to the fact that it is seen as the involvement of a person, group or organisation that influences and empowers enough people to follow and to bring about change in that area of life (Yukl 2010). A basic assumption in this understanding of leadership is that this kind of influencing and empowerment takes place in real-life situations and face-to-face contact between leaders and followers. The question that the article probes is, taking into account these basic assumptions about leadership, whether one can speak of ‘virtual leadership’ where there is not necessarily face-to-face contact between the leaders and the followers. I argue that it is indeed possible to speak of some kind of leadership and endeavour to investigate the so-called echurch as a case in point. An interview with the leader of the echurch in South Africa, Stephan Joubert, was published recently in the newspaper Die Kerkbode. It was this article that initiated the interest of the researcher to do some further exploration into this practical-theological phenomenon.